20 Impact of physician-staffed helicopters on patient outcomes: a systematic review. (26th April 2019) - Draegert, C; Risgaard, B; Baekgaard, JS; Steinmetz, J; Rasmussen, LS
Abstract : Background: Management of pre-hospital patients remains a challenge. In developed countries a physician-staffed helicopter emergency medical service (PS-HEMS) is used in addition to ground emergency medical service (GEMS), but the effect is debated. This systematic review aimed to evaluate the effect of PS-HEMS compared to GEMS on patient outcome, primarily mortality. Method: PubMed, EMBASE, and the Cochrane Library were systematically searched on October 15, 2018 for prospective, interventional studies comparing outcomes of patients treated and/or transported by either PS-HEMS or GEMS. Outcomes of interest were mortality, time to hospital, and quality of life (QoL). Results: Of 16 studies eligible for inclusion, 12 reported on trauma patients, four on cardiac patients, and one study on stroke patients. Three studies showed significantly different mortality rates (all on trauma patients) with lower 30 day mortality (OR=0.68 [0.47–0.98] and OR=0.41 [0.2–0.87]) and lower in-hospital mortality (OR=0.29 [0.1–0.82]) for PS-HEMS compared to GEMS. Eight studies showed significantly different time to hospital between patients transported with PS-HEMS compared to GEMS. In cardiac patients, time was significantly lower (84 vs 102 min and 71 vs 78 min, both p<0.01). Amongst trauma patients, three showed decreased time with PS-HEMS and three showed increased time. Three studies reported QoL on trauma patients, but no benefit of PS-HEMS was found. Conclusion: In this systematic review we found a possible survival benefit for trauma patients treated and transported with PS-HEMS compared to GEMS. Furthermore, we found that time to hospital was significantly reduced in cardiac patients transported with PS-HEMS compared to GEMS. Conflict of interest: None. Funding: Departmental.